(untitled) (Quaestiones Disputatae: temas en debate, 2017)
This work compares the concepts of the problem of identity and decolonialisation with regards to the Katarista-Indianista beliefs and decolianisation theory. Both converge to see this phenomenon as an historical legcay that articulates politcal domination, oppression, discrimation and the alienation of your own identity as a result: but the decolonial focus framed the problem in a long lasting geopolitical framework, the formation of modernity, eurocentrism and capitalism, thanks to it’s distinction between colonialism and coloniality. This difference has great consequences when the process of decolonilisation is considered, due to the fact that the decolonial ideologies suggest that the norm is to have a “different” society, distinct from the one that has been formed by the two parts of modernity and coloniality and based on interculturality, whilst the way of thinking of the Katarista-Indianista is heterogeneous.